Plague and Pregnancy: Why Special Considerations Are Needed. (21st May 2020) - Meaney-Delman, Dana; Oussayef, Nadia L; Honein, Margaret A; Nelson, Christina A
Abstract: Pregnant women are an important at-risk population to consider during public health emergencies. These women, like nonpregnant adults, may be faced with the risk of acquiring life-threatening infections during outbreaks or bioterrorism (BT) events and, in some cases, can experience increased severity of infection and higher morbidity compared with nonpregnant adults. Yersinia pestis, the bacterium that causes plague, is a highly pathogenic organism. There are 4 million births annually in the United States, and thus the unique needs of pregnant women and their infants should be considered in pre-event planning for a plague outbreak or BT event. Abstract : This commentary introduces key issues for pregnant women during a plague outbreak or bioterrorism event and summarizes 2 systematic reviews in this supplement that will inform clinical recommendations for treatment and prophylaxis of plague among pregnant women.